Golimumab in radiographic and nonradiographic axial spondyloarthritis: a review of clinical trials [Corrigendum] - Toussirot E; Vauchy C; Binda D; Michel F (Dove Medical Press, 2017)
Toussirot E, Vauchy C, Binda D, Michel F. Drug Des Devel Ther. 2016;10:2087–2094.On page 2089, a column heading in Table 1 was incorrectly presented. The last column heading was presented as “Golimumab 60 mg”, whereas this should have been presented as “Golimumab 100 mg” as shown below:Read the original article